1997
DOI: 10.1103/physreve.56.7204
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic wake fields and beam stability in slab-symmetric dielectric structures

Abstract: Several promising schemes for high-gradient acceleration of charged particles in slab-symmetric electromagnetic structures have been recently proposed. In this paper we investigate, by both computer simulation and theoretical analysis, the longitudinal and transverse wake fields experienced by a relativistic charged particle beam in a planar structure. We show that in the limit of an infinitely wide beam the net deflecting wake fields vanishes. This result is verified in the limit of a large aspect ratio ͑shee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
91
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 9 publications
5
91
0
2
Order By: Relevance
“…In this limit, the fundamental mode for the structure can be simply deduced from previous work on traveling waves in such a device found in Ref. 7. Inside of the gap (]YI < a ),we have for the fundamental symmetric mode…”
Section: )-Xmentioning
confidence: 97%
See 1 more Smart Citation
“…In this limit, the fundamental mode for the structure can be simply deduced from previous work on traveling waves in such a device found in Ref. 7. Inside of the gap (]YI < a ),we have for the fundamental symmetric mode…”
Section: )-Xmentioning
confidence: 97%
“…In addition, use of structures with slab, as opposed to cylindrical symmetry, gives the additional advantage of allowing a larger current to be loaded into the device without inducing excessive beam loading, as the accelerating beam can be spread out in the "wide" transverse dimension. Furthermore, it has been shown that use of a beam which is wide compared to the structure gap greatly suppresses the excitation of dipole modes in the device, thus enhancing the current which can be confidently accelerated before onset of the beam breakup instability [7]. Given these advantages, it was proposed in Ref.…”
mentioning
confidence: 99%
“…Therefore, the design of the DLW structures must compromise between a small transverse size to maximize the intensity of the wakefield, and a longer interaction length to maximize the energy gain of the test charge. An appealing solution consists of using flat electron beams passing through slab-geometry DLWs [14,[23][24][25]. This possibility has become more attractive since the recent advances toward generating flat beams directly in photoinjectors [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of this paper is to extend the formalism introduced in Ref. [14] by including all types of modes excited in a planar DLW. This paper is pedagogical in the sense that it is about the method of derivation rather than the results, which have been derived in previous papers, most extensively in Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation